Transcriptomic Insights into the Antifungal Effects of Magnolol on the Growth and Mycotoxin Production of Alternaria alternata - Liuqing Wang; Duo Wang; Shuzhi Yuan; Xiaoyuan Feng; Meng Wang (Toxins, 2020)
Alternaria alternata is an important phytopathogen causing fruit black rot and also producing a variety of mycotoxins, such as alternariol (AOH) and alternariol monomethyl ether (AME) as two main contaminants. This could lead to economic losses of agricultural products as well as human health risks. In this study, magnolol extracted from the traditional Chinese herb, Mangnolia officinalis, exhibited an obvious antifungal property and could completely suppress the mycelial growth at 100 μM. Morphological differences of A. alternata were observed to be significantly shrunk and wrinkled after the exposure to magnolol. Furthermore, AOH and AME were no longer produced in response to 50 μM of magnolol. To uncover the antifungal and antimycotoxigenic mechanisms, the transcriptomic profiles of A. alternata—treated with or without magnolol—were evaluated. The clustered genes responsible for AOH and AME biosynthesis were obviously less transcribed under magnolol stress and this was further confirmed by qRT-PCR. The global regulators of carbon and nitrogen utilization, such as CreA and NmrA, were significantly down-regulated and this possibly caused the reduction in mycotoxins. In addition, fatty acid β-oxidation was regarded to contribute to polyketide mycotoxin production for the supply of precursor acetyl-CoA while the expression of these related genes was inhibited. The response to magnolol led to the marked alteration of oxidative stress and the down-expression of the mitogen-activated protein kinase (MAPK) signaling pathway from the transcriptome data and the determination of peroxidase (POD), superoxide dismutase (SOD) and glutathione (GSH) assays. This above might be the very reason for the growth supression and mycotoxin production of A. alternata by magnolol. This study provides new insights into its potential as an important active ingredient for the control of A. alternata and its mycotoxins in fruits and their products.